piRBase: a web resource assisting piRNA functional study - Zhang, Peng (Database (Oxford), 2014)
piRNAs are a class of small RNAs that is most abundantly expressed in the animal germ line. Presently, substantial research is going on to reveal the functions of piRNAs in the epigenetic and post-transcriptional regulation of transposons and genes. A piRNA database for collection, annotation and structuring of these data will be a valuable contribution to the field, and we have therefore developed the piRBase platform which integrates various piRNA-related high-throughput data. piRBase has the largest collection of piRNAs among existing databases, and contains at present 77 million piRNA sequences from nine organisms. Repeat-derived and gene-derived piRNAs, which possibly participate in the regulation of the corresponding elements, have been given particular attention. Furthermore, epigenetic data and reported piRNA targets were also collected. To our knowledge, this is the first piRNA database that systematically integrates epigenetic and post-transcriptional regulation data to support piRNA functional analysis. We believe that piRBase will contribute to a better understanding of the piRNA functions. Database URL: http://www.regulatoryrna.org/database/piRNA/